Are formyl peptide receptors novel targets for therapeutic intervention in ischaemia–reperfusion injury? - Gavins, Felicity N.E. (Trends Pharmacol Sci, 2010)
Ischaemia–reperfusion (I/R) injury is a common feature of several diseases associated with high morbidity and mortality, such as stroke and myocardial infarction. The damaged tissue displays cardinal signs of inflammation and microvascular injury that, unless resolved, lead to long-term tissue damage with associated dysfunction. Current therapies are limited and are often associated with many side effects. Increasing evidence suggests that members of the formyl peptide receptor (FPR) family, in particular human FPR2/ALX, might have an important role in the pathophysiology of I/R injury. It was recently demonstrated that several peptides and non-peptidyl small-molecule compounds have anti-inflammatory and pro-resolving properties via their action on members of the FPR family. Here I review this evidence and suggest that FPR ligands, particularly in the brain, could be novel and exciting anti-inflammatory therapeutics for the treatment of a variety of clinical conditions, including stroke.